The Corporate Implications of Longer Lives - Gratton, Lynda; Scott, Andrew (MIT Sloan Management Review, 2017)
Across the world, people today are living longer. Whether it is in the United States, China, or Rwanda, average human life expectancy has increased over the past few decades. There is growing awareness that increasing longevity will have major implications for how people manage their work lives and careers. Rising life expectancy means the level of savings required to provide a reasonable income for retirement at age 65 is becoming increasingly infeasible for many people. Given the average level of savings, the authors say, many workers in their mid-40s are likely to need to work into their early to mid-70s; many currently in their 20s may work into their late 70s, and even into their 80s. Although people are starting to recognize that they will have to restructure their lives and careers, corporations are unprepared. Few organizations have taken full account of the opportunities and challenges longevity brings to their own workforces. Most companies, especially those operating in the advanced economies, still view life in terms of three stages: full-time education, full-time work, and then a "hard stop" retirement around the age of 65. This is the life structure that emerged in the 20th century and continues to underpin much thinking about the workforce. But in the view of the authors, it cannot be stretched to support a healthy 100-year life and will need to be expanded to include more stages. Without change, the authors argue, employees will struggle to build a working life that has resilience over an extended period of time and that will support a healthy and prosperous longevity. For example, as working lives become longer, the need for lifelong learning will increase. Skills and knowledge that are portable and externally accredited will be particularly valuable, the authors note, and individuals most likely to make successful transitions will be those with self-insight and diverse networks that provide alternative experiences and role models. One area the authors say is in serious need of reexamination is attitudes regarding older workers. In the next few decades, the authors expect there will be a fundamental rethinking of traditional corporate policies for recruitment, learning and development, compensation, and retirement. Corporations that move quickly to transform their policies will gain from employees who are more engaged and productive.
Keywords: Career development; Plan de carrière